A Disintegrin and Metalloprotease 10 Expressions Modulate Potential Metastatic and Thrombus Formation in Pancreatic Carcinoma - Miao Yu; Quan Chen; Qin Li; Yunfei Teng; Lin Xiao; Guang Yang; Chenxi Ouyang; Ahmed Mohammed Elamin Abdalla (Tehran University of Medical Sciences, 2022)
Background: Clinical investigations repurposing a disintegrin and metalloproteases 10 (ADAM10) as metastatic and thrombus marker have achieved encouraging results, but the mechanism behind this association remains unclear. Methods: This study was carried out in NingXia and Wuhan, China from 2017 to 2021. The effects of ADAM10 expression on the metastatic and thrombus-associated genes: tissue factor (TF), P-selectin glycoprotein ligand-1 (PSGL-1), cathepsin G (CTSG) and mucin 1 (MUC1) were examined by immunofluorescence, qRT-PCR and Western blotting analysis. Metastatic and thrombotic behaviors were evaluated using NODSCID mouse model. Results: The ADAM10 expression controlled the migration and invasion of pancreatic carcinoma cell-1(PANC-1), and significantly regulated the metastatic and thrombus-associated genes (P＜0.05). ADAM10 and MUC1 were regulated and aberrantly expressed by a dependent mechanism. Moreover, ADAM10 expression induced the progression of adenocarcinoma cells and thrombus formation in vivo. Conclusion: Regulation of ADAM10 expression in cancer cells might effectively pave the way for a more potent anti-metastatic and anti-thrombotic approach and could regulate the invasion and migration of cancer cells.